1990
DOI: 10.1530/jrf.0.0900063
|View full text |Cite
|
Sign up to set email alerts
|

Critical progesterone requirement for maintenance of pregnancy in ovariectomized rats

Abstract: The minimum progesterone concentration required to maintain the pregnancy was studied by varying doses of progesterone given subcutaneously to rats ovariectomized on Day 8 of pregnancy. Injecting 3 mg progesterone plus 200 ng oestradiol benzoate daily provided serum progesterone values between 25.4 +/- 7.0 and 35.2 +/- 6.2 ng/ml throughout Days 10-19 which were significantly lower than normal levels (P less than 0.05), but resulted in 93.6% of fetal survival on Day 19 which was not significantly different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…37 Achieving physiological levels of progesterone is a vital requirement to prevent any embryonic loss in oocyte retrieval operations. 40 Administration of supranormal levels of progesterone during early pregnancy caused reduction in the number of implantation and an increase in the preimplantation loss in mice. 41 Therefore, achieving low level of progesterone such as the level achieved by the present work, it could be advantageous in bringing the normal progesterone level and keeping the embryo safe.…”
mentioning
confidence: 99%
“…37 Achieving physiological levels of progesterone is a vital requirement to prevent any embryonic loss in oocyte retrieval operations. 40 Administration of supranormal levels of progesterone during early pregnancy caused reduction in the number of implantation and an increase in the preimplantation loss in mice. 41 Therefore, achieving low level of progesterone such as the level achieved by the present work, it could be advantageous in bringing the normal progesterone level and keeping the embryo safe.…”
mentioning
confidence: 99%
“…Terranova and Greenwald [29] demonstrated that A/LH was effective in terminating pregnancy on day 12 but the treatment was ineffective thereafter ( d a y 1 2 o f p r e g n a n c y i n T e r r a n o v a a n d Greenwald's study = day 11 of pregnancy in the present study). Adequate levels of progesterone are needed for maintaining pregnancy in many animals [30,31]. Terranova and Greenwald [32] demonstrated that plasma concentrations of progesterone after A/LH treatment on day 4 and 8 of pregnancy were lower than in control animals.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been discussed in greater detail (Arkaravichien & Kendle, 1992). Replacing progesterone in the ovariectomized rats prevented the increase in uterine contractions, recorded at 12 and 24 h. A dose of 4 mg day"1 was chosen for replacement as previous studies in this colony of rats showed that 3 mg day"1 gave serum progesterone concentrations lower than those in normal pregnant rats (Arkaravichien & Kendle, 1990). However, uterine contractions recorded at 36 and 48 h after ovariectomy in rats treated with progesterone plus oestradiol were different from those in intact animals injected with vehicle, possibly because the ovariectomized rats lacked some other myometrial inhibitory hormones produced by the ovary, such as relaxin.…”
Section: Ovariectomized Ratsmentioning
confidence: 99%
“…In our previous study (Arkaravichien & Kendle, 1990), it was shown that progesterone replacement in rats ovariectomized on day 15 of pregnancy could be delayed up to 36 h after ovariectomy, when uteri might have been contracting for quite a long period, without significant reduction in fetal viability. The present study investigated further the onset of active uterine contractions after progesterone withdrawal by injecting the anti¬ progestational steroid mifepristone and by ovariectomy in late pregnancy in rats and investigated the effects of prolonged uterine contractions after progesterone withdrawal on fetal viability and growth.…”
Section: Introductionmentioning
confidence: 97%